An investigation on factors influencing stress among UTAR students in Malaysia - Chong, Shu Hua; Loh, Wei Zhen; Ooi, Hui Jing (2023)
In general, stress can have a significant impact on various aspects of an individual's physical, mental, and emotional well-being.Nowadays, university students often experience high levels of stress due to various factors. According to the research, Malaysian university students were more likely to experience depression, anxiety, and stress.However, this research aims to identify and analyze the key factors influencing stress among university students. A comprehensive literature review was conducted to gather insights into the multifaceted nature of student stress. The study employed a primary data approach, including surveys and questionnaires, to collect data from a diverse sample of Universiti Tunku Abdul Rahman (UTAR) studentsin Malaysia. This research examines thatwhat are the factors influencing stress among Universiti Tunku Abdul Rahman (UTAR)students in Malaysia. This study consists of 5 independent variables, neuroticism (N), conscientiousness (C), self-expectation (SE), parental-expectation (PE)and social influence (SE). These independent variables are used to identify the relationship between stress among UTAR students. 440 sets of questionnaires were analysed through Statistical Package of Social Science (SPSS) 28.0 software. According to results, all independent variables(neuroticism, conscientiousness, self-expectation, parental expectation) are found to have significant relationship with stress among UTAR students, except for social influence resulting an insignificant relationship. This study also provides some recommendations and feedbackon improvingthe result and quality of the study in understanding the factor that affecting stress among university students. Therefore, this research will cover on the discussions of these factors that influencing stress among UTAR students.